Conceptions of quality as family resemblances. Issue 2 (21st May 2021) - Francis, Mark; Fisher, Ron; Song, Malin
Abstract : Purpose: To consider how quality should be conceptualized to improve understanding for researchers and practitioners, some researchers have discussed quality in terms of an essence or necessary condition. Others have regarded quality as individual and experiential, based on differences in actors' conceptions of quality. This paper aims to resolve the tension caused by these competing views and propose an appropriate method for future research in the area of quality. Design/methodology/approach: In many studies, researchers have attempted to understand quality in terms of necessary conditions or through a dualistic ontology. At the same time, an increasing number of researchers have emphasized its experiential nature while discussing quality in conjunction with meeting customers' expectations. This study investigates how quality can be understood using a conceptual framework based on family resemblances. Findings: There is no necessary condition or essence by which quality may be conceptualized or defined. This finding resolves the tension that has arisen from the simultaneous search for a common feature and the assertion that quality is experientially created by individuals. The research also highlights that the nature of quality may differ between people, time and place, or some aspects of it may be the same. Regarding quality in terms of family resemblances accommodates actors' different conceptions of quality. Phenomenography is proposed as an appropriate research approach with its focus on the qualitatively different ways in which actors make sense of phenomena in their lifeworld. Research limitations/implications: Understanding quality as a family of attributes, and using phenomenography as method, provides methodological clarity to long-standing research issues. Using the approaches outlined in this study will enable empirical studies of quality, in any context, to be conducted soundly and relatively quickly. It will also provide a more inclusive and holistic set of meanings based on the experiences of individuals. Practical implications: The research provides important insights for researchers and practitioners through clearer conceptions of quality. These include the ability to plan and deliver business outcomes that are more closely aligned with customers' expectations. Understanding the conceptions of quality, as experienced and determined through family resemblances, has clear implications for researchers and practitioners. Originality/value: Understanding actors' conceptions of quality through the lens of family resemblances resolves long-standing research issues. Using phenomenography as method is innovative, as it is an emerging research approach in the business domain.